The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1590/s0100-879x2000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, quality control, marketing and regulatory guidelines for herbal medicines (phytotherapeutic agents)

Abstract: This review highlights the current advances in knowledge about the safety, efficacy, quality control, marketing and regulatory aspects of botanical medicines. Phytotherapeutic agents are standardized herbal preparations consisting of complex mixtures of one or more plants which contain as active ingredients plant parts or plant material in the crude or processed state. A marked growth in the worldwide phytotherapeutic market has occurred over the last 15 years. For the European and USA markets alone, this will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
546
2
116

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 969 publications
(725 citation statements)
references
References 38 publications
8
546
2
116
Order By: Relevance
“…Studies have shown that there are several types of flavonoids that present biological activity, which produce significant anti-inflammatory (Calixto, 2000) and antimicrobial action (Schlemper et al, 1998;Sartori et al, 2003). Antimicrobial activity of the flavonoids is probably related to its capacity in complexing extracellular and soluble proteins such as structures from bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there are several types of flavonoids that present biological activity, which produce significant anti-inflammatory (Calixto, 2000) and antimicrobial action (Schlemper et al, 1998;Sartori et al, 2003). Antimicrobial activity of the flavonoids is probably related to its capacity in complexing extracellular and soluble proteins such as structures from bacterial cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…In 2008 Zhou et al analyzed caged xanthones possessing a unique 4-oxa-tricyclo[4.3.1.0 3,7 ]dec-2-one scaffold in the resin of Garcinia hanburyi (gamboges) (Fig. 1) [89].…”
Section: Phenols and Flavonoidsmentioning
confidence: 99%
“…As most productive sources, medicinal plants provide a large number of molecules that could be screened to find potential lead compounds for drug discovery [1,2]. Nowadays, the main concerns for the phytotherapeutics are the efficacy, safety and quality of phytomedicines [3,4]. Usually, a herb contains hundreds of chemical constituents but only a few components are bioactive [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the medicinal plants' usage has gradually abandoned the empirical method and become based on explicatory facts [1]. According to data from the World Health Organization (WHO), more than 80% of the population of developing countries still relies on medicine originating from natural plants as their main source of healthcare [2]. Globularia alypum L. is an aromatic and medicinal plant belonging to the Globulariaceae family, found throughout the Mediterranean area and largely used and considered for its therapeutic virtues [3].…”
Section: Introductionmentioning
confidence: 99%